Mechanisms and pathways for the clearance of bacteria from blood circulation in health and disease. Issue 2 (June 2016) - Minasyan, Hayk
Abstract: Available data do not support the concept that leukocytes engulf and kill bacteria in the bloodstream. Leukocytes cannot recognize or engulf bacteria in flowing blood; therefore, phagocytosis is impossible in the bloodstream and occurs instead outside of the bloodstream in the body tissues. Erythrocytes capture bacteria in the circulation using an electric charge and kill them using oxidation. The dead bacteria are then disintegrated and digested by the reticuloendothelial system (RES), particularly in the liver and the spleen